2011
DOI: 10.1111/j.1468-0351.2011.00424.x
|View full text |Cite
|
Sign up to set email alerts
|

Political objectives and privatization decisions

Abstract: In early Romanian privatization a group of firms was explicitly banned from privatization. We use this institutional feature to test which factors contributed to the selection of firms for long‐term state ownership, and find that politicians sheltered from privatization large and inefficient firms which paid low wages and had high overdue payments. These results are consistent with minimization of employment losses, even if efficiency enhancement of privatization had to be sacrificed. We conjecture that the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Thus a decline in employment may follow when the acquired companies are undergoing restructuring. Several studies found that employment in privatised firms usually falls, although in one study, jobs were saved when MNEs acquired ailing domestic firms (Szentpeteri & Telegdy, 2012;UNCTAD, 2004). Furthermore, acquisition oriented FDI could have adverse effects when MNEs close down acquired firms.…”
Section: Relative Performance Of Foreign-owned Subsidiaries and Domes...mentioning
confidence: 99%
“…Thus a decline in employment may follow when the acquired companies are undergoing restructuring. Several studies found that employment in privatised firms usually falls, although in one study, jobs were saved when MNEs acquired ailing domestic firms (Szentpeteri & Telegdy, 2012;UNCTAD, 2004). Furthermore, acquisition oriented FDI could have adverse effects when MNEs close down acquired firms.…”
Section: Relative Performance Of Foreign-owned Subsidiaries and Domes...mentioning
confidence: 99%